Rethinking the Comparative Study of Religious Ethics - Little, David (Journal of religious ethics, 2015)
This essay describes the author's change of approach to the comparative study of religious ethics from the one contained in a book on the subject (with Sumner B. Twiss), published in 1978. The change resulted from interactions with Abdulaziz Sachedina, the noted scholar of Islam, demonstrating the importance of comparing different ethical systems in reference to global topics like human rights, particularly the right to freedom of conscience.